Resilience, crisis management and continuous improvement against the impact of COVID-19 on employees' engagement and emotions. Insights from a Cypriot SME - Christina Nizamidou (Cogent Economics & Finance, 2023)
COVID-19 forced governments and organizations to navigate unchartered waters and shift to remote work to prevent its spreading, aiming to be resilient and maintain their sustainability. Recent research showed that COVID-19 impacted employees' engagement and emotions. As every crisis is unique and every organization experiences a crisis differently, this study adopts the single-case study research method to understand better how a Cypriot SME in the financial service dealt with COVID-19 and its aftermath. By interviewing multiple employees from all hierarchical levels, it assesses the company's level of resilience. Moreover, it demonstrates the company's challenges to preserve its commitment to continuous improvement and the implications of remote work on employees' engagement and emotions. Based on the findings, the company showed a high level of resilience, though it adopted a reactive behavior toward crisis management. These findings are beneficial as they expand on research on the importance of proactive behavior that advances continuous improvement and crisis preparedness. Additionally, it expands research about the implications of remote work. Lastly, by showing that their customers' financial sustainability directly influenced the company's financial sustainability due to COVID-19 and the ongoing Russo-Ukrainian War, the current offers novel insights about the impact of two mega-crises combined.
Keywords: 330; continuous improvement; COVID-19; crisis management; emotions; employees' engagement; remote work; resilience